Corporate Governance Strategies for Navigating the VUCA Era: A Case Study of BPRS Barokah Dana Sejahtera Yogyakarta - Edi Sunarto; Riduwan, Riduwan; Aftoni Sutanto (Universitas Ahmad Dahlan, 2025)
Introduction: Governance is a crucial aspect of financial institutions, including Islamic rural banks (BPR Syariah), to ensure sustainability and competitiveness. PT. BPR Syariah Barokah Dana Sejahtera faces challenges in governance implementation, particularly in the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) era. Several obstacles, such as inconsistency, insufficiently comprehensive governance guidelines, and lack of intensive socialization, hinder the effectiveness of governance practices. Purpose: This study aims to examine the implementation of governance at PT. BPR Syariah Barokah Dana Sejahtera and formulate strategies to optimize governance practices in response to the challenges of the VUCA era. Methodology: This research employs a qualitative approach with a case study method. Data were collected through observations, document analysis, and interviews. The analysis process follows a structured approach, including data collection, data reduction, data presentation, and conclusion verification. Findings: The study identifies key challenges in governance implementation, including inconsistency, incomplete governance guidelines, and inadequate socialization efforts. Strategies to strengthen governance in the VUCA era are explored, covering aspects such as self-assessment results, governance strengthening, technology and digitalization strategies, risk management, competitiveness enhancement through product innovation, collaboration and synergy strategies, as well as strategies for adapting to regulations and the business environment. Paper Type: Research Article. Keywords: BPR Syariah; Digitalization; Governance; Risk Management; Vuca.